Tacit Knowledge Mapping for Business Intelligence Analysis - Janna, Alisha Barqha (International Journal of Information Technology and Computer Science Applications, 2024)
The tacit knowledge in a higher institution, especially in university libraries, contains a series of intuition and inspiration that a librarian arises in exploring solutions to the various problems. Thus, limited sources of knowledge or information is a critical factor in the failure to provide accurate information. The main problem of the BI system is to capture tacit knowledge and use tacit knowledge as one of the data sources for data analysis to enhance the analytic results. The unstructured data can define as tacit knowledge in the form of data and information presented in the Knowledge Management System (KMS), and the cognitive business use both structured and unstructured data with highly sophisticated analytical techniques to identify, evaluate, and recommend a business plan of actions. The idea of being able to capture knowledge from different sources can be very beneficial to the BI system. This paper explored the solution to extracting tacit knowledge from librarians in order to enhance the data sources to be used in the BI by exploring the library's academic services, which use much tacit knowledge for answering questions with the requirement of data analysis as online or offline queries.